2011
DOI: 10.1103/physrevc.83.064902
|View full text |Cite
|
Sign up to set email alerts
|

Gluino production in ultrarelativistic heavy ion collisions and nuclear shadowing

Abstract: In this article we investigate the influence of nuclear effects in the production of gluinos in nuclear collisions at the LHC, and estimate the transverse momentum dependence of the nuclear ratios RpA = dσ(pA) dyd 2 p T /A dσ(pp) dyd 2 p T and RAA = dσ(AA) dyd 2 p T /A 2 dσ(pp) dyd 2 p T . We demonstrate that depending on the magnitude of the nuclear effects, the production of gluinos could be enhanced, compared to protonproton collisions. The study of these observables can be useful to determine the magnitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It remains to be seen if full next-to-leading-order (NLO) corrections can fill such a large gap between LO results and the CMS data, see also Refs. [12][13][14][15]. Although the relative importance of the NLO corrections is process-dependent, we recall that the NLO corrections enhance the LO NRQCD cross-section for single inclusive J/Ψ production by a factor about 10 [49], see also Refs.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen if full next-to-leading-order (NLO) corrections can fill such a large gap between LO results and the CMS data, see also Refs. [12][13][14][15]. Although the relative importance of the NLO corrections is process-dependent, we recall that the NLO corrections enhance the LO NRQCD cross-section for single inclusive J/Ψ production by a factor about 10 [49], see also Refs.…”
Section: Discussionmentioning
confidence: 99%
“…The gluinos are expected to be one of the most massive sparticles which constitute the MSSM and therefore their production is only feasible at a very energetic machine such as the Large Hadron Collider (LHC). The gluino production in nuclear collisions was presented at [35,74,76,98,99,100,101].Therefore one of the sources of CP violation in the MSSM arises from the gluinos sector. Some phenomenological studies about this case see [102].…”
Section: Gluinosmentioning
confidence: 99%
“…The influence of nonlinear gluon evolution in prompt photon production is estimated in Ref. [12], where we find an enhancement of the prompt photon cross section for LHC energies.…”
Section: Introductionmentioning
confidence: 54%
“…A LO QCD study of prompt photon production in pA and AA collisions including more recent nuclear pdf's is done in ref. [10], and it is shown that the amount of shadowing and antishadowing is very distinct for the various nuclear pdf's available, so these processes are usefull to discriminate among the different nuclear pdf's. Moreover, a precise knowledge of the gluon pdf's is crucial for a better understanding of the QCD evolution, mostly the possible nonlinear QCD evolution at small x and small Q 2 , where the gluon density in the nucleus becomes large and starts to saturate at momentum scales near Q sat (the so-called "saturation scale") [11].…”
Section: Introductionmentioning
confidence: 99%